Use of the Pelvic C-Clamp to Mitigate Acute Respiratory Distress Syndrome in a Patient with an Unstable Sacral Fracture - Michael J. DeRogatis; Paul S. Issack (Case Reports in Orthopedics)
Case. We present the case of a 21-year-old man who fell from a roof, sustaining a displaced sacral fracture with pelvic instability. He developed acute respiratory distress syndrome (ARDS) within 24 hours of injury. Placement of the pelvic C-clamp resulted in rapid resolution of pulmonary dysfunction, allowing for definitive internal fixation. Conclusion. The C-clamp is most commonly used to control hemorrhage in unstable posterior pelvic ring injuries. Our case demonstrates a rare use of the C-clamp to stabilize the posterior pelvis in a patient with an unstable sacral fracture and ARDS, to rapidly improve pulmonary function prior to definitive surgery.